Characterisation of combined abiotic and biotic stresses effects on lettuce plants via a multi-analysis approach - Bulgari, Roberta; Riahi, Jouhaina; Cecire, Riccardo; Celi, Luisella; Malandrino, Mery; Stefanescu Miralles, Gica; Comba, Lorenzo; Alfarano, Luca; Pugliese, Massimo (Frontiers in Plant Science, 2025)
Crop losses due to abiotic and biotic (in particular fungal diseases) stresses significantly impact yields and quality in agricultural productions. Identifying strategies to prevent or mitigate those stresses is crucial for developing resilient crop systems. To this aim, a deep and complete characterisation of the main effects induced in lettuce, a representative species grown in soilless system within a greenhouse, was conducted by applying water, nutritional, and biotic stresses individually and in combination. Specifically, water stress was induced on plants by 40% irrigation deficit with respect to the reference watering practice. Nutritional stress was induced by - 40% of nitrogen (N) and phosporus (P) in the nutrient solution. As biotic stress, the one induced by Fusarium wilt (caused by Fusarium oxysporum f. sp. lactucae) was considered. To characterise the effects on lettuce induced by the selected stresses, a wide set of analysis was performed, with a multidisciplinary approach: in vivo measurements involved spectral reflectance characterisation and chlorophyll assessment; at harvest, biotic stress severity quantification, based on vascular browning, was evaluated, and fresh and dry weight, chlorophylls, carotenoids, phenolics, anthocyanins, and nitrate, as well as macro, micro, and mesonutrients content were determined with destructive analysis. Results showed that Fusarium wilt had a greater effect on plants than water and nutrition stresses, reducing fresh weight (FW) by 69% while increasing antioxidants and nutrients, highlighting a shift toward stress-induced metabolic reactions. Spectral indices like Pigment Specific Simple Ratio (PSSRa) and Simple Ratio Pigment Index (SRPI) effectively detected the biotic stress, revealing significant differences between stressed and control plants, while there were no visual signs of stress or alterations in leaf color. The principal component analysis (PCA) highlighted FW, disease severity, and mineral content as key drivers of stress-induced changes, emphasizing the metabolic and physiological defense mechanisms of lettuce under biotic stress. These findings pave the way to the development of proactive, reliable, and effective methods for stress detection in lettuce cultivation, also including non-destructive optical approaches.